Ett attraktivt snittblomssortiment från perenner odlade på friland - Svensson, Anna (2008)
The production of cut flowers has diminished in Sweden and the remaining growers produce mainly in greenhouses. This situation could be changed if hardy, garden perennials suitable for Swedish conditions were to be used as cut flowers. A grower with suitable equipment as plastic tunnels or houses would be able to provide florists with an attractive assortment of perennials for cutting, during an extended selling period compared with the natural flowering period for these cultivars. This assortment would be based upon imported perennials already used by florists, but would also contain new products. To investigate the demand for locally field grown perennials as cut flowers, an inquiry took place. Ten florists were randomly selected and interviewed . They were all located to an area, 50 km radie, located from the southwest to the middle parts of Scania. The result shows that all the florists in the interview were very positive of using garden perennials in their profession. Several consumers regularly ask for seasonal cut flowers. They are also more aware of how the cut flowers are produced and transported over long distances.